1980
DOI: 10.6028/nbs.ir.80-2147
|View full text |Cite
|
Sign up to set email alerts
|

Daylighting, window management systems, and lighting controls

Abstract: This report investigates major factors concerning windows in buildings and their effect on visual conditions, thermal conditions, and energy requirements. Empirically obtained data are presented for daylight illumination as a function of solar radiation, sky condition, window size and orientation, and interior reflectance. The thermal and visual effects of several window management strategies are examined, along with an analysis of automatic lighting controls. Daylight utilization is seen to offer great potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…A building cooling load calculation procedure comparable in detail to the method outlined in Reference [20], Chapters 21,22,23, and 25 or Reference [25] shall be used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A building cooling load calculation procedure comparable in detail to the method outlined in Reference [20], Chapters 21,22,23, and 25 or Reference [25] shall be used.…”
Section: Discussionmentioning
confidence: 99%
“…Pumps shall be specified to provide proper and efficient performance. Selection and installation shall be in accordance with the requirements of the Hydraulic Institute, Reference [23] and local and nationally recognized codes and standards where applicable.…”
Section: Criterionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier measurements of diffuse Illuminance indicated a strong sensitivity to sky condition [9]. Diffuse illuminance levels were low for clear skies and completely overcast skies.…”
Section: Diffuse Illuminancementioning
confidence: 99%
“…Treado and Kusuda (1980) argue that if daylight entering through window can be used appropriately, controlled and dimmed, very large energy saving can be expected. Furthermore, it has been reported that, in daylight corridors, photoelectric lighting controls can give excellent energy savings ( Slater et al , 1996 ;Li and Lam, 2003 ).…”
Section: Daylight Controlmentioning
confidence: 99%